Analysis of COVID-19 infection in hemodialysis and kidney transplant patients in a pandemic hospital - Nurettin Ay; Ramazan Danış; Jehat Kılıç; Derya Deniz Altıntaş (Journal of Infection in Developing Countries)
Introduction: The mortality rate for any infection is often higher in patients with a kidney transplant (KT) and hemodialysis (HD), which may also be the case in novel coronavirus disease 2019 (COVID-19).